The impact of anti-cyclic citrullinated peptide antibody status on the management of patients with early rheumatoid arthritis: observational study results from Lithuania - Stropuvienė, Sigita; Baranauskaitė, Asta; Bukauskienė, Loreta; Zaikauskienė, Jolanta (Acta medica Lituanica, 2018)
Background. To provide data on the use of anti-cyclic citrullinated peptide antibody (anti-CCP) and other routinely used clinical parameters and to assess the impact of anti-CCP status on therapeutic decisions, an observational study was conducted in patients with rheumatoid arthritis (RA). Methods. Sixty-seven adult patients with a recent diagnosis of RA were recruited from four rheumatology centres in Lithuania and were prospectively observed for 12 months. Data collection was based on the review of medical records and routine examination of patients. Patients completed the Health Assessment Questionnaire – Disability Index and Patient Global Assessment of disease activity using a visual analogue scale. Physicians were asked about the importance of the anti-CCP results and other factors important for therapeutic decisions. Results. Of the 67 patients enrolled, 54 (80.6%) completed the study. At the beginning of the study, physicians considered anti-CCP results to be important for decision-making in 87.0% of patients. The perceived importance of anti-CCP results did not change significantly throughout the study. After one year of treatment, factors that were considered more important than the anti-CCP results included the presence of erosions, significantly increased C-reactive protein, duration of morning stiffness, multi-articular expanding, and rheumatoid factor status. For nearly half of the patients (n = 26; 48.1%), physicians would not change the treatment strategy if the patient had the opposite anti-CCP results at baseline. Conclusions. The study revealed that decision-making in the management of RA was based on multifactorial data. The role of anti-CCP as a single test in treatment decisions needs further investigation.
Keywords: rheumatoid arthritis; anti-CCP antibody; observational study